Environment-friendly flame-retardant engineering plastic for battery shell and preparation method of environment-friendly flame-retardant engineering plastic
By mixing specific proportions of polypropylene, ethylene-vinyl acetate copolymer, furan resin and other components, environmentally friendly flame retardant engineering plastics for battery shells, the problem of insufficient mechanical properties and corrosion resistance of engineering plastics for battery shells in the prior art is solved, and higher safety and service life are achieved.
Patent Information
- Application Number
- CN202411953600.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-25
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of engineering plastics, and in particular to an environmentally friendly flame-retardant engineering plastic for a battery shell and a preparation method thereof. Background Art
[0002] Engineering plastics have excellent comprehensive properties and can be used for a long time in harsh chemical and physical environments. They can replace metals as engineering structural materials. Engineering plastics are widely used in the automotive, mechanical, electronic and electrical fields, and construction and chemical industries. Especially in the electronic and electrical fields, engineering plastics can be used for wire and cable coating, battery shell materials, etc.
[0003] In daily use scenarios, batteries may be subjected to various external forces, such as being squeezed, collided, etc., which may cause the risk of electrolyte leakage. At the same time, the volume of the battery may slightly expand or shrink during use, which requires the engineering plastics used in the battery shell to have good mechanical properties and corrosion resistance. However, although the current engineering plastics have certain mechanical properties and corrosion resistance, their performance is limited.
[0004] Therefore, developing an engineering plastic for battery shells with good mechanical properties and corrosion resistance is of great significance for ensuring the safety of batteries and improving their service life. Summary of the invention
[0005] The present invention provides an environmentally friendly flame-retardant engineering plastic for a battery shell and a preparation method thereof, which solves the problem of poor mechanical properties and poor corrosion resistance of the environmentally friendly flame-retardant engineering plastic for a battery shell in the related art.
[0006] The technical solution of the present invention is as follows: The present invention provides an environmentally friendly flame-retardant engineering plastic for a battery shell, comprising the following components in parts by weight: 150 parts of polypropylene, 5-10 parts of ethylene-vinyl acetate copolymer, 15-25 parts of furan resin, 4-8 parts of dodecenyl succinic anhydride, 5-16 parts of wollastonite, 1-3 parts of clarifier, 1-2 parts of antioxidant, 10-15 parts of flame retardant; The furan resin includes furfuryl alcohol resin and furfural resin; The weight ratio of the furfuryl alcohol resin to the furfural resin is 1:19 to 19:1.
[0007] As a further technical solution, the weight ratio of the furfuryl alcohol resin to the furfural resin is 3~8:2.
[0008] When the weight ratio of furfuryl alcohol resin to furfural resin is 3~8:2, the mechanical properties and corrosion resistance of the environmentally friendly flame-retardant engineering plastics for battery shells can be further improved.
[0009] As a further technical solution, the wollastonite includes needle-shaped wollastonite and powdered wollastonite, and the weight ratio of the needle-shaped wollastonite to the powdered wollastonite is 1-3:1.
[0010] In the present invention, wollastonite includes powdered wollastonite and needle-shaped wollastonite. The two wollastonites of different shapes are used together to better fill the gaps in the plastic matrix, thereby making the internal structure of the material more compact, thereby further improving the mechanical properties and corrosion resistance of the environmentally friendly flame-retardant engineering plastics for battery shells. By adjusting the content ratio of powdered wollastonite and needle-shaped wollastonite, when the weight ratio of needle-shaped wollastonite to powdered wollastonite is 1 to 3:1, the mechanical properties and corrosion resistance of the environmentally friendly flame-retardant engineering plastics for battery shells can be further improved.
[0011] As a further technical solution, the wollastonite is modified wollastonite, and the raw materials of the modified wollastonite include wollastonite, benzofuran-6-carboxylic acid and polyvinyl pyrrolidone.
[0012] In the present invention, benzofuran-6-carboxylic acid and polyvinyl pyrrolidone are used to modify wollastonite, which can improve the dispersion performance of wollastonite in the plastic matrix, so that wollastonite can better interact with other components, thereby further improving the mechanical properties and corrosion resistance of the environmentally friendly flame-retardant engineering plastics for battery shells.
[0013] As a further technical solution, the weight ratio of wollastonite, benzofuran-6-carboxylic acid and polyvinyl pyrrolidone is 40:1:2-5.
[0014] When the weight ratio of wollastonite, benzofuran-6-carboxylic acid and polyvinyl pyrrolidone is 40:1:2-5, the mechanical properties and corrosion resistance of the environmentally friendly flame-retardant engineering plastics for battery shells can be further improved.
[0015] As a further technical solution, the preparation method of the modified wollastonite comprises the following steps: dispersing the benzofuran-6-carboxylic acid and the polyvinyl pyrrolidone in dimethylformamide, adding the wollastonite, dispersing evenly, and drying to obtain the modified wollastonite.
[0016] As a further technical solution, the transparent agent is a sorbitol transparent agent, preferably bis(3,4-dimethylbenzylidene)sorbitol.
[0017] As a further technical solution, the antioxidant is one or more of antioxidant 168, antioxidant 1076, and antioxidant 1098.
[0018] As a further technical solution, the flame retardant is one or more of antimony trioxide, magnesium hydroxide, and triethyl phosphate.
[0019] The present invention also proposes a method for preparing the environmentally friendly flame-retardant engineering plastic for a battery shell, comprising the following steps: uniformly mixing the components in parts by weight, extruding and granulating, and obtaining the environmentally friendly flame-retardant engineering plastic for a battery shell.
[0020] As a further technical solution, during the extrusion, the temperature is 160-180°C.
[0021] The working principle and beneficial effects of the present invention are: In the present invention, polypropylene, ethylene-vinyl acetate copolymer, furan resin, dodecenyl succinic anhydride, wollastonite, a transparent agent, a flame retardant and an antioxidant are combined to prepare an environmentally friendly flame-retardant engineering plastic for a battery shell with good flame retardancy and transparency, and good mechanical properties and corrosion resistance. Among them, furan resin is added to the raw material, and the furan resin includes furfuryl alcohol resin and furfural resin. By using two different furan resins together, the resin material of the engineering plastic can be tightly combined to form a stable internal structure, so that the prepared environmentally friendly flame-retardant engineering plastic for a battery shell has good mechanical properties and corrosion resistance, and can resist the action of external forces and the erosion of corrosive substances. DETAILED DESCRIPTION
[0022] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0023] In the following embodiments and comparative examples, the model of polypropylene is NZ30S; the model of ethylene-vinyl acetate copolymer is EVA 18J3; the model of furfuryl alcohol resin is PB02740; the model of furfural resin is LBW-0236, purchased from Hubei Langbowan Biomedicine Co., Ltd.; the needle-shaped wollastonite has an aspect ratio of 15:1; the particle size of the powdered wollastonite is 325 mesh; the model of polyvinyl pyrrolidone is K60.
[0024] Example 1 An environmentally friendly flame-retardant engineering plastic for a battery shell comprises the following components in parts by weight: 150 parts of polypropylene, 5 parts of ethylene-vinyl acetate copolymer, 15 parts of furan resin, 4 parts of dodecenyl succinic anhydride, 5 parts of needle-shaped wollastonite, 1 part of bis(3,4-dimethylbenzylidene)sorbitol, 1 part of antioxidant 168, and 10 parts of magnesium hydroxide; The furan resin includes 0.75 parts of furfuryl alcohol resin and 14.25 parts of furfural resin; The preparation method comprises the following steps: uniformly mixing the above components in parts by weight, extruding and granulating to obtain environmentally friendly flame-retardant engineering plastics for battery shells; wherein, during extrusion, the extrusion temperature of zone one is 160°C, the extrusion temperature of zone two is 180°C, and the extrusion temperature of zone three is 170°C.
[0025] Example 2 An environmentally friendly flame-retardant engineering plastic for a battery shell comprises the following components in parts by weight: 150 parts of polypropylene, 10 parts of ethylene-vinyl acetate copolymer, 25 parts of furan resin, 8 parts of dodecenyl succinic anhydride, 16 parts of needle-shaped wollastonite, 3 parts of bis(3,4-dimethylbenzylidene)sorbitol, 2 parts of antioxidant 168, and 15 parts of magnesium hydroxide; The furan resin includes 23.75 parts of furfuryl alcohol resin and 1.25 parts of furfural resin; The preparation method comprises the following steps: uniformly mixing the above components in parts by weight, extruding and granulating to obtain environmentally friendly flame-retardant engineering plastics for battery shells; wherein, during extrusion, the extrusion temperature of zone one is 160°C, the extrusion temperature of zone two is 180°C, and the extrusion temperature of zone three is 170°C.
[0026] Example 3 The only difference between this embodiment and embodiment 2 is that, in this embodiment, the furan resin includes 13 parts of furfuryl alcohol resin and 12 parts of furfural resin.
[0027] Example 4 The only difference between this embodiment and embodiment 2 is that in this embodiment, the furan resin includes 15 parts of furfuryl alcohol resin and 10 parts of furfural resin.
[0028] Example 5 The only difference between this embodiment and embodiment 2 is that in this embodiment, the furan resin includes 20 parts of furfuryl alcohol resin and 5 parts of furfural resin.
[0029] Example 6 The only difference between this embodiment and embodiment 5 is that in this embodiment, the needle-shaped wollastonite is replaced by an equal amount of powdered wollastonite.
[0030] Example 7 The only difference between this embodiment and embodiment 5 is that, in this embodiment, 16 parts of needle-shaped wollastonite are replaced by 6 parts of needle-shaped wollastonite and 10 parts of powdered wollastonite.
[0031] Example 8 The only difference between this embodiment and embodiment 5 is that, in this embodiment, 16 parts of needle-shaped wollastonite are replaced by 14 parts of needle-shaped wollastonite and 2 parts of powdered wollastonite.
[0032] Example 9 The only difference between this embodiment and embodiment 5 is that, in this embodiment, 16 parts of needle-shaped wollastonite are replaced by 8 parts of needle-shaped wollastonite and 8 parts of powdered wollastonite.
[0033] Example 10 The only difference between this embodiment and embodiment 5 is that, in this embodiment, 16 parts of needle-shaped wollastonite are replaced by 12 parts of needle-shaped wollastonite and 4 parts of powdered wollastonite.
[0034] Embodiment 11 The only difference between this embodiment and embodiment 10 is that in this embodiment, the wollastonite is modified wollastonite, and its preparation method includes the following steps: dispersing 2 parts of benzofuran-6-carboxylic acid in 55 parts of dimethylformamide, adding 40 parts of wollastonite (the weight ratio of needle-shaped wollastonite to powdered wollastonite is 3:1), dispersing evenly, and drying to obtain modified wollastonite.
[0035] Example 12 The only difference between this embodiment and embodiment 10 is that in this embodiment, the wollastonite is modified wollastonite, and its preparation method includes the following steps: dispersing 2 parts of polyvinyl pyrrolidone in 55 parts of dimethylformamide, adding 40 parts of wollastonite (the weight ratio of needle-shaped wollastonite to powdered wollastonite is 3:1), dispersing evenly, and drying to obtain modified wollastonite.
[0036] Example 13 The only difference between this embodiment and Embodiment 12 is that, in this embodiment, the wollastonite is modified wollastonite, and its preparation method comprises the following steps: dispersing 1 part of benzofuran-6-carboxylic acid and 1 part of polyvinyl pyrrolidone in 55 parts of dimethylformamide, adding 40 parts of wollastonite (the weight ratio of needle-shaped wollastonite to powdered wollastonite is 3:1), dispersing evenly, and drying to obtain modified wollastonite.
[0037] Embodiment 14 The only difference between this embodiment and embodiment 13 is that in this embodiment, 6 parts of polyvinyl pyrrolidone are added.
[0038] Embodiment 15 The only difference between this embodiment and embodiment 13 is that in this embodiment, 2 parts of polyvinyl pyrrolidone are added.
[0039] Example 16 The only difference between this embodiment and embodiment 13 is that in this embodiment, 5 parts of polyvinyl pyrrolidone are added.
[0040] Comparative Example 1 The only difference between this comparative example and Example 1 is that in this comparative example, the furan resin only includes furfuryl alcohol resin.
[0041] Comparative Example 2 The only difference between this comparative example and Example 1 is that in this comparative example, the furan resin only includes furfural resin.
[0042] Comparative Example 3 The only difference between this comparative example and Example 1 is that in this comparative example, furan resin is not added.
[0043] Experimental Example 1 Flame retardant performance test The environmentally friendly flame-retardant engineering plastics for battery shells prepared in Examples 1 to 5 were subjected to oxygen index determination according to the test method in GB / T 2406.2-2009 "Determination of Combustion Behavior of Plastics by Oxygen Index Method Part 2: Room Temperature Test", wherein, during the test, method A (top surface ignition method) was adopted, the specimen was a type I specimen with a size of 110 mm × 10 mm × 4 mm, and the test results were the average of the three specimens, with the results retaining one decimal place. The test results are shown in Table 1 below.
[0044] Table 1 Flame retardant performance test results of Examples 1 to 5
[0045] It can be seen from Table 1 that the oxygen index of the environmentally friendly flame-retardant engineering plastic samples for battery shells of Examples 1 to 5 is greater than 30.0%, indicating that the environmentally friendly flame-retardant engineering plastic for battery shells prepared in this scheme has good flame retardant properties.
[0046] Experimental Example 2 Mechanical Properties Test The environmentally friendly flame retardant engineering plastics for battery shells prepared in Examples 1 to 16 and Comparative Examples 1 to 3 were tested for tensile properties according to the test method in GB / T 1040.1-2018 "Determination of Tensile Properties of Plastics Part 1: General Principles", wherein the test speed was 50 mm / min during the test, and the test result was the average value of 5 samples.
[0047] Experimental Example 3 Corrosion resistance test The environmentally friendly flame-retardant engineering plastics for battery shells prepared in Examples 1 to 16 and Comparative Examples 1 to 3 were subjected to a salt spray test. After the samples were exposed to a salt spray test chamber containing 6 wt % sodium chloride for 96 h, the tensile strength was tested after the corrosion test according to the above-mentioned tensile strength test method, and the tensile strength change rate was tested according to the following formula: tensile strength change rate (%) = (tensile strength before corrosion test - tensile strength after corrosion test) / tensile strength before corrosion test × 100%. The test result is the average of 5 samples, and the result is retained to 2 decimal places.
[0048] The performance test results of Experimental Examples 2 and 3 are shown in Table 2 below: Table 2 Performance test results of Examples 1 to 16 and Comparative Examples 1 to 3
[0049] It can be seen from Table 2 that compared with Comparative Examples 1 to 3, the tensile strength of Example 1 is significantly improved, and the rate of change of tensile strength is significantly reduced, indicating that when furan resin is added to the raw material, and the furan resin includes furfuryl alcohol resin and furfural resin, the environmentally friendly flame retardant engineering plastics for the prepared battery shell can have good mechanical properties and corrosion resistance by using two different resins in combination.
[0050] Compared with Examples 2 to 3, the tensile strength of Examples 4 to 5 is improved and the change rate of tensile strength is reduced, indicating that when the weight ratio of furfuryl alcohol resin to furfural resin is 3 to 8:2, the mechanical properties and corrosion resistance of the environmentally friendly flame retardant engineering plastics for battery shells can be further improved.
[0051] Compared with Examples 5 to 6, the tensile strength of Examples 7 to 10 is improved, and the change rate of tensile strength is reduced, indicating that when the wollastonite includes powdered wollastonite and needle-shaped wollastonite, the mechanical properties and corrosion resistance of the environmentally friendly flame-retardant engineering plastics for battery shells can be further improved. Compared with Examples 7 to 8, the tensile strength of Examples 9 to 10 is improved, and the change rate of tensile strength is reduced, indicating that when the weight ratio of needle-shaped wollastonite to powdered wollastonite is 1 to 3:1, the mechanical properties and corrosion resistance of the environmentally friendly flame-retardant engineering plastics for battery shells can be further improved.
[0052] Compared with Examples 10 to 12, the tensile strength of Examples 13 to 16 is improved and the change rate of tensile strength is reduced, indicating that when wollastonite is modified together with benzofuran-6-carboxylic acid and polyvinyl pyrrolidone, the mechanical properties and corrosion resistance of the environmentally friendly flame-retardant engineering plastics for battery shells can be further improved.
[0053] Compared with Examples 13 to 14, the tensile strength of Examples 15 to 16 is improved and the rate of change of tensile strength is reduced, indicating that when the weight ratio of wollastonite, benzofuran-6-carboxylic acid and polyvinyl pyrrolidone is 40:1:2 to 5, the mechanical properties and corrosion resistance of the environmentally friendly flame-retardant engineering plastics for battery shells can be further improved.
[0054] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. An environmentally friendly flame-retardant engineering plastic for a battery shell, characterized in that: The composition comprises the following components in parts by weight: 150 parts of polypropylene, 5-10 parts of ethylene-vinyl acetate copolymer, 15-25 parts of furan resin, 4-8 parts of dodecenyl succinic anhydride, 5-16 parts of wollastonite, 1-3 parts of clarifier, 1-2 parts of antioxidant, 10-15 parts of flame retardant; The furan resin includes furfuryl alcohol resin and furfural resin; The weight ratio of the furfuryl alcohol resin to the furfural resin is 1:19 to 19:
1.
2. The environmentally friendly flame-retardant engineering plastic for battery shell according to claim 1, characterized in that: The weight ratio of the furfuryl alcohol resin to the furfural resin is 3-8:
2.
3. The environmentally friendly flame-retardant engineering plastic for battery shell according to claim 1, characterized in that: The wollastonite includes needle-shaped wollastonite and powdered wollastonite, and the weight ratio of the needle-shaped wollastonite to the powdered wollastonite is 1-3:
1.
4. The environmentally friendly flame-retardant engineering plastic for battery shell according to claim 1, characterized in that: The wollastonite is modified wollastonite, and the raw materials of the modified wollastonite include wollastonite, benzofuran-6-carboxylic acid and polyvinyl pyrrolidone.
5. The environmentally friendly flame-retardant engineering plastic for battery shell according to claim 4, characterized in that: The weight ratio of the wollastonite, benzofuran-6-carboxylic acid and polyvinyl pyrrolidone is 40:1:2-5.
6. The environmentally friendly flame-retardant engineering plastic for battery shell according to claim 4, characterized in that: The preparation method of the modified wollastonite comprises the following steps: dispersing the benzofuran-6-carboxylic acid and the polyvinyl pyrrolidone in dimethylformamide, adding the wollastonite, dispersing evenly, and drying to obtain the modified wollastonite.
7. The environmentally friendly flame-retardant engineering plastic for battery shell according to claim 1, characterized in that: The transparent agent is a sorbitol transparent agent.
8. The environmentally friendly flame-retardant engineering plastic for battery shell according to claim 1, characterized in that: The antioxidant is one or more of antioxidant 168, antioxidant 1076, and antioxidant 1098.
9. The environmentally friendly flame-retardant engineering plastic for battery shell according to claim 1, characterized in that: The flame retardant is one or more of antimony trioxide, magnesium hydroxide and triethyl phosphate.
10. A method for preparing an environmentally friendly flame-retardant engineering plastic for a battery shell according to any one of claims 1 to 9, characterized in that: The steps include: mixing the components in parts by weight uniformly, extruding and granulating, and obtaining the environmentally friendly flame retardant engineering material for battery shell. plastic.